If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + 5 = 3p + 9 Reorder the terms: 5 + 8p = 3p + 9 Reorder the terms: 5 + 8p = 9 + 3p Solving 5 + 8p = 9 + 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 5 + 8p + -3p = 9 + 3p + -3p Combine like terms: 8p + -3p = 5p 5 + 5p = 9 + 3p + -3p Combine like terms: 3p + -3p = 0 5 + 5p = 9 + 0 5 + 5p = 9 Add '-5' to each side of the equation. 5 + -5 + 5p = 9 + -5 Combine like terms: 5 + -5 = 0 0 + 5p = 9 + -5 5p = 9 + -5 Combine like terms: 9 + -5 = 4 5p = 4 Divide each side by '5'. p = 0.8 Simplifying p = 0.8
| 40=5z+16 | | 4-2(a+6)=-22 | | x-1+1/4=-6 | | 1/2t=36 | | 4.2x-4.5=3.9 | | X-4/10=13955 | | x-1/2=1+1/4 | | X-4/10 | | -3-(-5-1)= | | x+32=2x-8 | | 6x+8=11y+19 | | x-3=-5+1/2 | | 1x+40=2.5x | | x+32=-2x-8 | | 54.8-1/5d=60.2 | | 5n=6x+10 | | 9a-4(2a/5)= | | 1.5x+40=2.5x | | -134-6x=12x+100 | | -3x^2-6x+12=0 | | 5-6d=-11 | | 5-6d=-7 | | 4/7x=140 | | -4u^2-33u-35=0 | | 49-14x+x^2+x^2=65 | | 4.2(y+18)=65.1 | | 5(u-2)-8u=14 | | 7y=3x-12 | | y=cosh(ln(9x^3)) | | 3x+15=6x-14 | | 5.1e+1.07=9 | | 10x-14=7+11x |